2009
DOI: 10.1177/104063870902100403
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Intramammary Infections at Dry-off Based on Sampling Strategy, Epidemiology of Pathogens, and Agreement Beyond Chance

Abstract: Abstract. Isolation of pathogens from duplicate or multiple milk samples is currently considered the gold standard in diagnosis of bovine intramammary infections (IMI). However, in large field studies and especially in normal dairy production conditions, collection of single samples is often the most practical option to determine the causal agents of mastitis in a herd. The objective of the present study was to determine how well results between the first and the second sample in pairs of duplicate and success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…Routine prevalence studies based upon detection of Staphylococci in milk during lactation find it difficult to differentiate between incidental transient infection or contamination during milking procedures and the existing infections. This study avoids this error by taking only those organisms present during the dry period into consideration [ 18 ]. The percentage (27.9) of phenotypic resistance of Staphylococci to oxacillin detected in our study was similar to reports from Uruguay (22%) [ 19 ] and Argentina (27.6%) [ 20 ], but lower than for Korea (60.2%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Routine prevalence studies based upon detection of Staphylococci in milk during lactation find it difficult to differentiate between incidental transient infection or contamination during milking procedures and the existing infections. This study avoids this error by taking only those organisms present during the dry period into consideration [ 18 ]. The percentage (27.9) of phenotypic resistance of Staphylococci to oxacillin detected in our study was similar to reports from Uruguay (22%) [ 19 ] and Argentina (27.6%) [ 20 ], but lower than for Korea (60.2%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced in a metaanalysis published in 2002, there has been little consistency in defining either the inoculum volume, the number of samples, or colony-forming units (CFU) required to define any type of IMI. 5 However, a recently published report 15 proposed standard microbiologic definitions of IMI caused by major and minor pathogens based on single quarter milk samples. In addition to the current lack of standardized definitions of IMI, much of the information used to describe S. aureus IMI has been collected from experimental infections.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, the utility of colony count in assessing IMI status, comparing duplicate samples collected at dry-off, was examined, and investigators reported that an IMI could be diagnosed accurately with a single sample when CFU was considered, and that the required number of CFU for a positive diagnosis was dependent on the type of pathogen identified. 15 In that study, the investigators established the utility of a single sample positive with at least 1 CFU of S. aureus/0.01 ml in identifying S. aureus IMI. The current study, examining naturally occurring infections repeatedly over time, supports the investigators' conclusion that a single colony is sufficient to diagnose a S. aureus IMI using single quarter sample.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BC seems to be a useful, but imperfect test to diagnose IMI (Erskine and Eberhart 1988;Sanford et al 2006). Still, it is often seen as the best available method (Torres et al 2009) and is therefore used as the reference test in many evaluations of other tests, such as SCC, and is also frequently used in practice. Latent class analysis was used to estimate the sensitivity of BC.…”
Section: Bacteriological Culturementioning
confidence: 99%